Sicherheit ist machbar!: das Heidelberger Audit-Konzept für urbane Sicherheit, am Beispiel der Kommunalen Kriminalprävention in Pforzheim - Hermann, Dieter; Wachter, Egon; Kerner, Hans-Jürgen (Tübinger Schriften und Materialien zur Kriminologie, 2022)
Promoting the objective and subjective safety of residents is an important field of action in municipal policy. Crime and fear of crime can affect the quality of life, people's attitudes toward crime policy and economic decisions about the choice of location. For a security- and citizen-oriented municipality, the reduction of crime and the reduction of fear of crime must therefore be primary goals. The instrument "Community Crime Prevention" and the further developed „Heidelberg Audit Concept for Urban Security“ (HAKUS) offer the possibility to achieve these goals. The central elements of this audit-instrument include the regular recording of the objective and subjective security situation as well as the knowledge-based implementation and evaluation of prevention measures. By using the security audit, it is possible to focus prevention measures on city districts and groups of people with a high fear of crime and to select measures that influence the most influential conditions of fear of crime. In this way, municipal resources can be used effectively and efficiently. The city of Pforzheim conducted the first survey in 2019 to improve the safety. 2.230 residents (out of 8.000 people surveyed) answered a 12-page questionnaire and returned it. The response rate of almost 28 percent is high for a written survey. The respondents listed more than 3.500 free-text suggestions for improving the quality of life. This shows the high interest of Pforzheim residents in safety issues. The following publication presents the individual findings of the survey in a differentiated manner. These are interpreted in consideration of regional and supra-regional conditions. Overall, the results of the survey show that the crime prevention projects already implemented by the municipality cover a large part of the causes of fear. Pforzheim is on the right way with its crime prevention. However, it can still be improved by the results of the survey. Concrete suggestions are shown.